2016
DOI: 10.1016/j.jfma.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Using acute kidney injury severity and scoring systems to predict outcome in patients with burn injury

Abstract: Our results revealed that AKI stage has considerable discriminative power for predicting mortality. Compared with other prognostic models, AKI stage is easier to use to assess outcome in patients with severe burn injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…RRT was reported in 13 studies (4357 patients) with consecutive sampling of patients and used in 12 (8–16) % of all burn patients (Additional file 10). RRT modes were continuous RRT [38, 45, 46, 54, 55], intermittent haemodialysis [47], or unspecified [27, 28, 34, 37, 48, 50, 58].…”
Section: Resultsmentioning
confidence: 99%
“…RRT was reported in 13 studies (4357 patients) with consecutive sampling of patients and used in 12 (8–16) % of all burn patients (Additional file 10). RRT modes were continuous RRT [38, 45, 46, 54, 55], intermittent haemodialysis [47], or unspecified [27, 28, 34, 37, 48, 50, 58].…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] AKI also predict higher mortality in patients with burns but has not been incorporated into most burn-specific scoring systems. [ 14 17 , 34 , 35 ] Yang et al found that early elevation of plasma or urine neutrophil gelatinase–associated lipocalin is associated with early AKI and mortality. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…We also found that higher ABSI score was associated with poorer survival. In addition to the burn-specific scoring system, various scoring systems used in the ICU predict outcome in burn patients [ 4 , 7 , 17 , 40 , 41 ]. Although these scoring systems do not incorporate burn-specific information, they have predictive ability because they are representatives of the overall condition of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute kidney injury (AKI) is a common, harmful complication with an incidence rate ranging from 28% to 75% in a hospital setting. [ 1 4 ] AKI-related adverse effects can potentially be controlled by early intensive intervention. Stevens–Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and SJS/TEN overlap syndrome are potentially fatal disorders characterized by high fever, widespread blistering exanthema of macules, and atypical target-like lesions, accompanied by mucosal involvement with a mortality rate of 10% for SJS and more than 30% for TEN.…”
Section: Introductionmentioning
confidence: 99%